Distinguishing spinocerebellar ataxia with pure cerebellar manifestation from multiple system atrophy (MSA-C) through saccade profiles. Issue 1 (January 2017) - Terao, Yasuo; Fukuda, Hideki; Tokushige, Shin-ichi; Inomata-Terada, Satomi; Yugeta, Akihiro; Hamada, Masashi; Ugawa, Yoshikazu
Highlights: We studied saccade profiles in spinocerebellar ataxia and multiple system atrophy patients. The velocity profiles help to differentiate the two disorders. The difference may represent braking and accelerating deficits in the disorders. Abstract: Objective: Patients with spinocerebellar ataxia with pure cerebellar presentation (SCD) and multiple system atrophy (MSA-C) show similar symptoms at early stages, although cerebellofugal pathology predominates in SCD, and cerebellopetal pathology in MSA-C. We studied whether saccade velocity profiles, which reflect the accelerating and braking functions of the cerebellum, can differentiate these two disorders. Methods: We recorded visually guided (VGS) and memory guided saccades (MGS) in 29 MSA-C patients, 12 SCD patients, and 92 age-matched normal subjects, and compared their amplitude, peak velocity and duration (accelerating and decelerating phases). Results: Hypometria predominated in VGS and MGS of MSA-C, whereas hypometria was less marked in SCD, with hypermetria frequently noted in MGS. Peak velocity was reduced, and deteriorated with advancing disease both in SCD and MSA-C groups at smaller target eccentricities. The deceleration phase was prolonged in SCD compared to MSA-C and normal groups at larger target eccentricities, which deteriorated with advancing disease. Conclusion: Saccades in MSA-C were characterized by a more prominent acceleration deficit and those in SCD by a more prominent braking defect, possibly caused by the cerebellopetal and cerebellofugal pathologies, respectively. Significance: Saccade profiles provide important information regarding the accelerating and braking signals of the cerebellum in spinocerebellar ataxia.